LEAN MANAGEMENT MEETS KNOWLEDGE MANAGEMENT: A CRITICAL REVIEW OF IMPLEMENTATION STRATEGIES FOR SMALL ENTERPRISES - Alomari, Ali Saeed (The journal of contemporary issues in business and government, 2024)
This article critically explores the integration of lean management principles within knowledge management processes in small enterprises, a topic that remains underexplored despite its potential to significantly enhance organizational efficiency and innovation. The adoption of lean principles—traditionally applied in manufacturing contexts such as eliminating waste, continuous improvement, and optimizing value—into knowledge management can be particularly transformative for small businesses, which often operate under resource constraints. Through a literature review and analysis of case studies, this review identifies effective strategies and common challenges encountered by small enterprises. The article discusses the theoretical adaptations necessary for applying lean principles to knowledge processes and provides practical insights from successful implementations. It concludes with a discussion on the future implications of this integration, offering both research directions and recommendations for small enterprise managers eager to optimize their knowledge management practices. This critical examination not only highlights the synergies and conflicts between lean management and knowledge management but also proposes a framework for small enterprises seeking to capitalize on these methodologies to foster a competitive edge.